Effectiveness and Efficiency of Waste Banks in Ambarawa District Semarang Regency in 2023 - Ariyadi, Dony; Siwiendrayanti, Arum (Universitas Diponegoro, 2024)
Ambarawa District, which is one of the districts with the highest density in Semarang Regency, experiences waste problems. Based on the official website of the Semarang Regency Environmental Agency, there are 10 active waste banks spread throughout Ambarawa District, including Acil, Rengas Asri, Mawar Asri, Mukti Bareng, Tegal Asri, Projo, Sari Asri, Tanjung Asri, Bina Lingkungan, and Bina Mandiri. The type of research used in this study was a case study based on quantitative data with a descriptive approach. Data analysis in this study uses the calculation of the Overall Equipment Effectiveness (OEE) equation and elasticity index. Based on the results obtained, 10 waste banks are located in Ambarawa District. The overall waste bank at OEE is less than 60%, and the elasticity index value is less than 1, which indicates that the effectiveness and efficiency of waste banks in Ambarawa District are low. In addition, the performance of waste banks in Ambarawa District is relatively low.